2020
DOI: 10.1111/flan.12443
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of direct and indirect synchronous written corrective feedback: Learning outcomes and students' perceptions

Abstract: From a sociocultural perspective, collaborative writing tasks offer opportunities to negotiate in decision‐making processes while also sharing responsibility for the production of a single text (Storch, 2013, Collaborative writing in L2 classrooms. Bristol: Multilingual Matters). Although research has found benefits for such tasks (Storch, 2019, Lang Teach, 52, 40–59; Taguchi & Kim, 2016, Appl Linguist, 37, 416–437), variation in how different types of synchronous written corrective feedback (SWCF) in such a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 43 publications
2
28
2
Order By: Relevance
“…This indicates that most students rated highly the usefulness of the collaborative correcting process they had experienced. Although this finding is supported by previous research reporting students' acknowledgement of the effects of teacher feedback on accuracy improvement (Ferris, 1995;Kim et al, 2020;Montgomery & Baker, 2007;Saito, 1994), it elaborates on the teacher's mediation and peer collaboration. The findings are supplemented by the eight students' reported benefits of correction, which are in line with MLE's transcendence.…”
Section: Theme 1: Evaluation Of Effectivenesssupporting
confidence: 59%
See 1 more Smart Citation
“…This indicates that most students rated highly the usefulness of the collaborative correcting process they had experienced. Although this finding is supported by previous research reporting students' acknowledgement of the effects of teacher feedback on accuracy improvement (Ferris, 1995;Kim et al, 2020;Montgomery & Baker, 2007;Saito, 1994), it elaborates on the teacher's mediation and peer collaboration. The findings are supplemented by the eight students' reported benefits of correction, which are in line with MLE's transcendence.…”
Section: Theme 1: Evaluation Of Effectivenesssupporting
confidence: 59%
“…Student perceptions of teacher feedback have long been researched in L2 writing studies, yet these have reported inconclusive findings. Students perceived that the teacher's written corrections and comments helped improve their writing accuracy (Ferris, 1995;Kim, Choi, Kang, Kim, & Yun, 2020;Montgomery & Baker, 2007;Saito, 1994). In particular, Malaysian university students acknowledged that teacher feedback on content and organization of their written texts is more useful than feedback on vocabulary and grammar (Vasu, Ling, & Nimehchisalem, 2016).…”
Section: Brief Review Of Feedback Research Into Learners' Perceptionsmentioning
confidence: 99%
“…Unlike Shintani and Aubrey (2016), which utilized on-line systems, Kim et al (2020) examined the role of direct (i.e. offering the correct forms) and indirect (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, of the two target structures examined, the effect of indirect feedback was more pronounced on the past perfect tense than on articles. More recently Kim et al (2020) compared the impact of direct and indirect written CF on 53 beginner learners of L2 Korean targeting 12 linguistic features. They found that direct written CF was more useful in helping students produce accurate writing, but both feedback types were effective in promoting the learning of new linguistic features through collaborative writing.…”
Section: Literature Reviewmentioning
confidence: 99%